(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This paper examines the complex jurisprudence of the Court of Cassation regarding compensation for late diagnosis of terminal illnesses. It also analyzes taxonomic aspects, distinguishing damages for the premature loss of life, compensable iure proprio to relatives, from damages for the loss of survival chances, which compensate for the uncertain but concrete possibility of a longer life. The aim of this paper is to outline the relevant jurisprudential framework and address the delicate issues of quantification and compensation for damages, establishing any incompatibilities, barring exceptional circumstances.